2020
DOI: 10.1016/j.bja.2020.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Supporting more than one patient with a single mechanical ventilator: useful last resort or unjustifiable risk?

Abstract: A first case of meningitis/encephalitis associated with SARS-Coronavirus-2. Int J Infect Dis 2020; 94: 55e8 26. Practice Advisory for the Prevention. Diagnosis and management of infectious complications associated with neuraxial techniques. Anesthesiology 2017; 126: 585e601 27. Harrop-Griffiths W. You can't be too careful …or can you?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Furthermore, this scheme is not intended as a permanent solution for ventilating multiple patients, and should be used only with hospital administration approval and acknowledgement of the unique ethical considerations during a crisis (such as the COVID-19 pandemic). 11,12 Although the COVID-19 pandemic inspired our designs, it may have utility in other mass casualty scenarios such as natural disasters, terrorist attacks, and battlefield medicine. Future versions should aim to extend to more than two patients per ventilator.…”
mentioning
confidence: 99%
“…Furthermore, this scheme is not intended as a permanent solution for ventilating multiple patients, and should be used only with hospital administration approval and acknowledgement of the unique ethical considerations during a crisis (such as the COVID-19 pandemic). 11,12 Although the COVID-19 pandemic inspired our designs, it may have utility in other mass casualty scenarios such as natural disasters, terrorist attacks, and battlefield medicine. Future versions should aim to extend to more than two patients per ventilator.…”
mentioning
confidence: 99%
“…Testing outlined in this paper took place using the aforementioned sophisticated critical care ventilator, but the system has also been tested on a broad range of ventilators and can be utilised with any ventilatory source that is capable of Pressure Control Ventilation. As is common to many similar systems, the use of Volume Control Ventilation can result is unpredictable delivery of tidal volumes to each limb and therefore risks hyperinflation of areas of lung tissue [18] . This forms an obvious and important area for further research, as lung protective ventilation has been shown in both trials and reviews [19] to reduce mortality in ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…There are many limitations to this approach, and it has even led some organisations to issue joint statements against its use [20] . Employing this solution demands a high level of sophisticated knowledge, staff training, and usually comes with significant restriction regarding the ability to alter respiratory parameters for each patient [18] . As such, the authors do not endorse or advocate ventilator sharing as a normal course of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…38 There was some support in the literature for what could be the very last resort for ventilator support: bifurcating or splitting an anesthesia machine between 2 patients. 39 , 40 As part of a system, as well as having the backup of New York State emergency supplies, neither of these last 2 options: anesthesia machines or bifurcation ever became a consideration.…”
Section: Planning For Surge: What Additional Equipment and Supplies Wmentioning
confidence: 99%